Let's perform the long division of \( 4x^3 + 12x^2 + 19x + 7 \) by \( 2x + 12 \).
Use Long Division: \[ \begin{array}{r|l} & 2x^2 + 6x + 1 \ \hline 2x + 12 & 4x^3 + 12x^2 + 19x + 7 \ & - (4x^3 + 24x^2) \ \hline & -12x^2 + 19x + 7 \ & + (12x^2 + 72x) \ \hline & -53x + 7 \ & + (53x + 636) \ \hline & -629 \ \end{array} \]
-
Divide the first term: \[ \frac{4x^3}{2x} = 2x^2 \]
-
Multiply: \[ 2x^2 \cdot (2x + 12) = 4x^3 + 24x^2 \]
-
Subtract: \[ (4x^3 + 12x^2) - (4x^3 + 24x^2) = -12x^2 \]
-
Bring down the next term: \[ -12x^2 + 19x \]
-
Divide the first term: \[ \frac{-12x^2}{2x} = -6x \]
-
Multiply: \[ -6x \cdot (2x + 12) = -12x^2 - 72x \]
-
Subtract: \[ (-12x^2 + 19x) - (-12x^2 - 72x) = 91x \]
-
Bring down the last term: \[ 91x + 7 \]
-
Divide the first term: \[ \frac{91x}{2x} = 45.5 \text{ (Or } \frac{91}{2}\text{)} \]
-
Multiply: \[ 45.5 \cdot (2x + 12) = 91x + 546 \]
-
Subtract: \[ (91x + 7) - (91x + 546) = -539 \]
So, the final result of the long division is:
\[ \text{Quotient: } 2x^2 - 6x + 45.5 \] \[ \text{Remainder: } -539 \]
Thus, we can express the answer as:
\[ \text{Answer: } 2x^2 - 6x + 45.5 \quad \text{with remainder } -539 \]